KONTEKSTUALISASI PEMBELAJARAN BAHASA ARAB PERSPEKTIF FILSAFAT ILMU - Nisa, Nathasa Khoirun; Bakar, M. Yunus Abu; Ratnaningtyas, Oktavia (Irfani, 2026)
This research aims to contextualize Arabic language learning in Indonesia through the perspective of philosophy of science in order to reconstruct the traditional textual paradigm and overcome the gap between theoretical mastery (nahwu-sharaf) and applicable communicative competence. This research uses a library research method with a qualitative-philosophical approach. The research design is analytical-critical, examining and reconstructing the learning paradigm through in-depth conceptual analysis. The data analysis technique is carried out by content analysis and philosophical reflection on related primary and secondary sources, which are synthesized based on the three pillars of philosophy of science: ontology, epistemology, and axiology. The results of the study are analyses that produce a holistic reconstruction of the Arabic language learning paradigm. Ontologically, Arabic is understood not as a static entity but as a dynamic, plural living reality (acknowledging Fusha and 'Ammiyyah), and culturally bound. Epistemologically, language knowledge is actively constructed by students through social interaction and authentic experiences with inductive-communicative methods, shifting away from passive knowledge transfer. Axiologically, the value of learning extends beyond narrow religious and academic goals to include pragmatic (career, economic), intercultural, and intellectual (critical thinking) values. The synthesis of these three pillars results in a contextual learning model that is student-centered, uses authentic materials, and is oriented towards pragmatic competencies for real life.